Faculty Perceptions of Building Collaborative Teaching Capacities within a Transnational Virtual Exchange: A Collaborative Autoethnography - Weaver, Gregory; Hiltebrand, Genevieve; Ngai, Grace; Chan, Stephen (Journal of International Students, 2022)
The 2019/2020 academic year brought historic opportunities for faculty to manage virtual exchanges (O’Dowd, 2021), yet limited research exists on how teachers develop their capacity within these programs. As educators collaborating on a transnational virtual exchange, we aim to investigate the process that teachers go through as they co-develop and collaborate in a transnational virtual exchange from our experiences and perceptions. We ask: To what extent do previous lived experiences mediate the process of teacher capacity building in a transnational virtual, collaborative exchange? This collaborative qualitative autoethnography case study explores our experiences as four instructors from the United States and Hong Kong, reflecting our experiences as they relate to teacher capacity building in transnational virtual exchange. The data suggests that previously lived international experiences assisted the instructors in capacity building within a virtual exchange and brought into question the role of cultural humility.